EKSISTENSI 212 MART SOEBRANTAS KOTA PEKANBARU - Hasanah, Nur; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The thesis writing entitled â€œThe Existence of 212 Mart Soebrantas Pekanbaru Cityâ€ began with the writerâ€™s interest in the existence of Sharia Cooperative 212 minimarket retailer. Where the ownership is in congregation, it is managed professionally and centrally to maintain its competitiveness in terms of distribution, production, price and promo networks. In line with that many companies have sprung up in the field of retail trade in the form of shops, supermarkets, minimarkets and others. With the increasing acceptance of the existence of minimarkets or supermarkets in the community, making business owners and investors compete and attract as many consumers as possible so that more enthusiasts. This research was conducted at 212 Mart Jl. HR. Soebrantas, Tampan District, Panam Pekanbaru City. The purpose of this research is to find out the 212 Mart Soebrantas adaptation strategy in developing its progress from other minimarkets. The approach used in this research is a qualitative descriptive approach. And the selection of informants is done by using purposive sampling technique, namely the acquisition of data from informants based on certain criteria or restrictions, namely managers and employees of 212 Mart Soebrantas who have been running this business for approximately 3 years. The data collection techniques used in this study are observation, interview and documentation techniques. The theory used in this research is the adaptation strategy theory by Edi Suharto. The final conclusion of this study states that the adaptation strategy contained in the 212 Mart Soebrantas business consists of 3 parts: active, passive and network strategies. These three strategies are used and are mutually binding with the 212 Mart Soebrantas business, thus being able to provide a way to develop business and be able to defend the business of 212 Mart Soebrantas from various pressures, obstacles and competition. Â Keywords : 212 Mart Soebrantas Ritel, Existence.